3D Printing in Eye Care - Larochelle, Ryan D. (Ophthalmol Ther, 2021)
Three-dimensional printing enables precise modeling of anatomical structures and has been employed in a broad range of applications across medicine. Its earliest use in eye care included orbital models for training and surgical planning, which have subsequently enabled the design of custom-fit prostheses in oculoplastic surgery. It has evolved to include the production of surgical instruments, diagnostic tools, spectacles, and devices for delivery of drug and radiation therapy. During the COVID-19 pandemic, increased demand for personal protective equipment and supply chain shortages inspired many institutions to 3D-print their own eye protection. Cataract surgery, the most common procedure performed worldwide, may someday make use of custom-printed intraocular lenses. Perhaps its most alluring potential resides in the possibility of printing tissues at a cellular level to address unmet needs in the world of corneal and retinal diseases. Early models toward this end have shown promise for engineering tissues which, while not quite ready for transplantation, can serve as a useful model for in vitro disease and therapeutic research. As more institutions incorporate in-house or outsourced 3D printing for research models and clinical care, ethical and regulatory concerns will become a greater consideration. This report highlights the uses of 3D printing in eye care by subspecialty and clinical modality, with an aim to provide a useful entry point for anyone seeking to engage with the technology in their area of interest.